National Health Interview Survey, 1989: Health Insurance Supplement ([Verlag nicht ermittelbar], 1992)
The basic purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. The 1989 Health Insurance Supplement provides 93 variables from the core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1989 [ICPSR 9583]) including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. It also contains summary variables from the Health Conditions, Doctor Visits, and Hospital Episode files of the 1989 NHIS. The 53 variables unique to this supplement include the type of health insurance program the respondent was covered by (including public assistance programs), extent of coverage, reasons for not carrying health insurance, and effects of job loss on coverage.